Arabie du Sud pendant la Grande Guerre - Ferwagner, Péter Ákos (Études sur la Région Méditerranéenne, 2023)
The southern part of the Arabian Peninsula was a low-intensity conflict zone, one of the secondary theatres of the First World War. Even compared to other fronts in the Middle East (Caucasus, Dardanelles, Mesopotamia, Palestine/Syria), its importance was minimal. Nevertheless, the fighting here was not insignificant. What was at stake in these struggles was mainly whether the British or the Ottomans controlled the trade routes through the Red Sea and the Indian Ocean. In the end, the British emerged victorious from the struggle, bringing virtually all of South Arabia under their control. The only exception was Yemen, which managed to preserve its independence, although it was accompanied by the continuation of extremely archaic conditions.